A comparative analysis on the morphology and electrochemical performances of solution-casted and electrospun PEO-based electrolytes: The effect of fiber diameter and surface density. (1st February 2021) - Banitaba, Seyedeh Nooshin; Semnani, Dariush; Karimi, Mohammad; Heydari-Soureshjani, Elahe; Rezaei, Behzad; Ensafi, Ali A.
Abstract: Solvent-free polymer electrolytes have been prepared through standard electrospinning and solution casting techniques, respectively. A series of nanofibrous electrolytes with various average fiber diameters and different surface densities were electrospun. In addition, polymeric films were casted with several thicknesses. It was shown that crystalline regions as well as fraction of free lithium ions were enhanced by fabrication of the finer fibers. The solution-casted electrolytes with the higher thicknesses displayed lower free ions and less amorphous phases. The nanofibrous mats illustrated the ionic conductivity from 0.062 to 0.172 mS.cm −1 .While, the solution-casted ones presented lower ionic conductance in the range of 0.006 to 0.008 mS.cm −1 . As surface density of the nanofibrous and solution-casted mats increased, the bulk resistance was improved. Moreover, it was identified that the prepared solvent-free electrolytes obeyed the Arrhenius behavior. The nanofibrous and solution-casted electrolytes with the highest ionic conductivities showed the highest values for the dielectric parameters. Furthermore, the optimum as-spun membrane illustrated higher specific capacity and Faradic current density compared with the solution-casted one. The results implied that the electrospun membranes are good candidates for solvent-free electrolyte application in the Li-ion batteries.